Effects of Calcium Hydroxide Intracanal Medications on T Helper (Th1, Th2, Th9, Th17, and Tfh) and Regulatory T (Treg) Cell Cytokines in Apical Periodontitis: A CONSORT RCT - Teixeira, Flavia F.C. [UNESP]; Cardoso, Flavia G.R. [UNESP]; Ferreira, Nadia S. [UNESP]; Corazza, Bruna J.M. [UNESP]; Valera, Marcia M.C. [UNESP]; Nascimento, Gustavo G.; Martinho, Frederico C. (Elsevier, 2022)
Introduction: This Consolidated Standards of Reporting Trials randomized clinical trial investigated T helper (Th1, Th2, Th9, Th17, and Tfh) and regulatory T (Treg) cell–type cytokines and their networks in apical periodontitis (AP). We also assessed the effects of calcium hydroxide [Ca(OH)2] intracanal medications (ICMs) on helper T and Treg cell–type cytokines. Methods: Twenty teeth with primary endodontic infection and apical periodontitis were randomly divided into two groups: Ca(OH)2 + saline solution (n = 10) and Ca (OH)2 + 2% chlorhexidine-gel (n = 10). Samples were collected from the periradicular tissue fluid (PTF) before (PTFs1) and after 14 days of ICMs (PTFs2). The Human High Sensitivity T Cell Panel was used to quantify target T-helper (Th)1: interelukin (IL)-2, IL-12, and interferon-gamma (IFN-γ); Th2: IL-4, IL-5, and IL-13; Th9: IL-9; Th17: IL-17; T follicular helper cells (Tfh): IL-21; and Treg-cell-type cytokine: IL-10. Results: Th1-type cytokines were higher than Th2-type ones, at PTFs1. Positive (+) associations were found among all Th1-type cytokines and all Th2-type cytokines. There were negative (-) correlations between all Th1- and Th2-type cytokines. Size of radiolucent lesions and symptoms (tenderness to percussion and/or pain on palpation) were positively correlated with Th1-type cytokines, IL-17, and IL-21 but negatively correlated with Th2-type cytokines and IL-10 (all, P <.001). Both ICMs increased Th2-type cytokines and IL-10 (P <.05) and decreased Th1-type cytokines, IL-17, and IL-21 (P <.05), with no differences among them (P >.05). Conclusions: Complex T-cell cytokine networks are involved in AP. Both Ca(OH)2 ICMs effectively increased IL-4, IL-5, IL-10, and IL-13 and lowered IL-2, IL-12, IL-17, IL-21, and IFN-γ.
Keywords: Cytokines; endodontics; inflammation; intracanal medication; root canal; T-helper